PATTERNS OF ECONOMIC AND SOCIAL INEQUALITY IN DIFFERENT COUNTRIES: A LITERATURE REVIEW - Redi Yana Kapisa; Ayi Maulana (Prosiding Seminar Nasional Indonesia, 2025)
Inequality is a complex and multidimensional global phenomenon, with varying levels and characteristics among countries with different levels of development. Common trends identified include the increase in inequality in recent decades, the link between inequality and differential access to opportunities, and the negative impact of inequality on economic growth, socio-political stability and people's well-being. The review concludes that a comprehensive and inclusive approach is needed to address economic and social inequality. This should involve collaboration between the government, private sector, and civil society in implementing policies that promote equity, such as progressive tax reforms, investment in education and skills training, expanded access to healthcare and social protection, and the promotion of inclusive and sustainable economic growth. In addition, efforts are needed to strengthen governance, fight corruption, and promote transparency and accountability in public decision-making.